Comic Contracts 2.0 – Contracts that Have (and Give) a Voice - Ketola, Anne; de Rooy, Robert; Haapio, Helena (Ledizioni, 2024)
Composite Comic Contracts are the next iteration of contract design, building on the development of legally binding visual contracts, known as Comic Contracts. Making contracts and contractual rights digitally accessible and understandable affords agency and access to justice for the cognitively vulnerable. We describe the creative and contracting processes and discuss the benefits and challenges from a cognitive-linguistic perspective and from a Proactive Contracting legal and interpretive perspective. By enhancing engagement, comprehension and retention of information, Composite Comic Contracts provide the essential preconditions for cognitive accessibility and the success of any contractual relationship with cognitively vulnerable people. We argue that elusive legal certainty on potential legal interpretive issues should not be a barrier to legal innovation and legal design. Composite Comic Contracts are not only contracts that have a voice, but also ones that give a voice.
Keywords: fi=Talousoikeus|en=Business Law|